University EFL Students’ Problem in Speaking Skill and What Teacher Suggest - Susanti, Galuh; Aini, Nafisah Nur; Puspitasari, Evi (Proceeding Universitas Muhammadiyah Yogyakarta Graduate Conference, 2020)
Speaking skill is one of the four skills which must be mastered properly because it is related to student's communication skills. This study was conducted to find most frequently problems faced by EFL students in speaking English and to explore teachers’ suggestion to encounter the problems. With the participation of 100 university students, a questionnaire was distributed to get the quantitative data. Meanwhile the second research objective was reached by interviewing 2 EFL teachers. Instruments used to conduct this mixed-method are a questionnaire from an expert and an interview protocol. The results will unveil the most common problems faced by EFL students and how to encounter the problems based on teachers’ view-points. The result of the research will be discussed by connecting to relevant literature. Suggestion and limitation faced while doing this research will also presented.